2018
DOI: 10.1111/jam.13930
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fishmeal inclusion and prebiotic supplementation on the hindgut faecal microbiota of farmed Tasmanian Atlantic salmon (Salmo salarL.)

Abstract: This study highlights the importance of the new fish feeds for promoting salmon health in aquaculture industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Through a seasonal study, Hatje et al (2014) reported that the persistence and prevalence of Vibrio and Pseudomonas species in the gut of Atlantic salmon were caused mainly by water temperature. Similarly, previous studies showed that lactic acid bacteria (LAB) count of hindgut feces of Atlantic salmon decreased in response to elevated water temperatures (Neuman et al 2016(Neuman et al , 2018.…”
Section: Water Temperature and Salinitymentioning
confidence: 67%
“…Through a seasonal study, Hatje et al (2014) reported that the persistence and prevalence of Vibrio and Pseudomonas species in the gut of Atlantic salmon were caused mainly by water temperature. Similarly, previous studies showed that lactic acid bacteria (LAB) count of hindgut feces of Atlantic salmon decreased in response to elevated water temperatures (Neuman et al 2016(Neuman et al , 2018.…”
Section: Water Temperature and Salinitymentioning
confidence: 67%
“…A complete assessment of diet composition would comprise a review in itself, especially because different diets are aimed at maximising different traits in salmon. We defer to various other studies on this issue (Gillund and Myhr 2010, Hixson et al 2014, Davidson et al 2016, Emery et al 2016, Harvey et al 2016, McMeans et al 2017, Caballero-Solares et al 2018, Neuman et al 2018, Weihe et al 2018, Foroutani et al 2020, Lovmo et al 2021, Gaffney and Lavery 2022, Goglio et al 2022.…”
Section: Feeding Regimesmentioning
confidence: 96%
“…Decreased protein turnover with down-regulation of adaptive and innate immune response genes [160] Agri-pro (not specified) Atlantic salmon Limited effect on microbiome and LAB [161] scFOS, XOS, GOS Sea bass scFOS and XOS increased the number of OTUs and species richness; 7 days was sufficient to modulate allochthonous gut microbiota [162] scFOS, XOS Sea bass…”
Section: Of Prebiotics Nucleotides Vitamin C and E Atlantic Salmonmentioning
confidence: 99%